Calliaxina chalmasii (Brocchi, 1883) comb. nov. (Decapoda: Axiidea: Callianassidae: Eucalliacinae), a ghost shrimp from the Middle Miocene of Europe, with reappraisal of the fossil record of Eucalliacinae - Hyžný, Matúš (Zootaxa, 2012)
A detailed study of chelipeds of two Middle Miocene burrowing ghost shrimp taxa, Callianassa chalmasii Brocchi, 1883,and Callianassa rakosiensis Lőrenthey, 1897, based on isolated propodi revealed that they are conspecific—the latterspecies is based on the minor cheliped of the former species. Material coming from several roughly coeval localities ofAustria (early ’Badenian’), Hungary (late ’Badenian’) and Slovakia (early ’Sarmatian’) provided sufficient data forredescription of C. chalmasii and its reassignment to the genus Calliaxina (subfamily Eucalliacinae). As such it is the firstrecognized representative of the genus in the fossil record. It is argued that for the Eucalliacinae, the following featuresare diagnostic: a square P1 manus usually converging distally, the presence of a ridge on the lateral surface at the base offixed finger, and a relatively short fixed finger, often with a triangular tooth. For reliable generic assignment within the Eucalliacinae both chelipeds (propodi), major and minor, should be present.